(3afhf GdbQGAI hegGQGJ GdGJUGd aj VhA efgL JcGedj (B/s - (3Ydj, ceGd RYaQs ((3GdOeGe (B[(3GdSYhOjI(B] (3;s (3LOI(B:s (3GdQjGV (B:s (3ecJHI GdeJfHj,s, 2020)
(3jgOa gPG GdcJGH Edi JfejI egGQGJ GdbQGAI hGdEJUGd GddZhj ddWGdH GdLGeYj HWQjbI YedjI JWHjbjI eJOQLI, JHOC HJCcjO Gdeaghe GdMOjK ddbQGAI GdPj jYJeO Ydi (B: (3GdJYQa hGdfWb, hGdage hGdfbO, hGdehGRfI hMd GdeTcdGJ, Ke GdJQcjR Ydi egGQGJ Gdage GdYejb deG jbQC ShGA eG Hjf GdSWhQ Ch eG hQGAgG (B: (3djUd Edi OQLI Jecfg ef GdJbhje hGdJMdjd hGdESJfJGL, hGdEQJaGY Hg Edi eSJhi GdbQGAI GdfGbOI hJeMjU eG jbQC, ajJe JOQjHg Ydi GSJNOGe egGQGJg GdYbdjI (B: (3djchf dg JacjQg GdfGbO, hQCjg GdeSJbd heG jJejR Hg ef hVhM hObI, heQhfI haGYdjI, hOGaYjI hefWbjI, hgh eG jYcS bOQJg Ydi GdJacjQ ajeG jYJbO hjYed(B.s
(3HHdjhLQGajI (B: (3UaMI (B290-291.s
Keywords: (3GdbQGAIs -- (3JWHjbGJs; (3GdeMGOKIs; (3GdGJUGd (B((3Yde GLJeGY(B)s